2013
DOI: 10.2174/1874943720130912001
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Injection Therapy (Prolotherapy) for Hip Labrum Lesions: Rationale and Retrospective Study

Abstract: Abstract:Background: Acetabular labral tear is a debilitating condition for which there are few effective non-surgical treatment options. A number of studies in humans and in animal models suggest that the labrum may have a capacity for spontaneous healing, and that therapies that seek to exploit and facilitate this process may be beneficial. Regenerative injection therapies have shown promise in the treatment of several musculoskeletal disorders, but have not previously been applied to labral tear. Methods:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…It is thought to work through a cellular mechanism that induces the production of new collagen by stimulating an inflammatory reaction. 1,30,31 A gentle irritant solution injected to a localized area creates a mild, controlled injury that stimulates the body's natural healing mechanisms to develop new collagen fibers, resulting in tightening of the weakened structure. 26,30,46,60 Additional treatments repeat this process, allowing a gradual build-up of tissue to restore the original strength of the area.…”
Section: Case Description Historymentioning
confidence: 99%
“…It is thought to work through a cellular mechanism that induces the production of new collagen by stimulating an inflammatory reaction. 1,30,31 A gentle irritant solution injected to a localized area creates a mild, controlled injury that stimulates the body's natural healing mechanisms to develop new collagen fibers, resulting in tightening of the weakened structure. 26,30,46,60 Additional treatments repeat this process, allowing a gradual build-up of tissue to restore the original strength of the area.…”
Section: Case Description Historymentioning
confidence: 99%
“…Again, smallscale evidence is available about the efficacy of this treatment for the management of hip labral tears. In a case series of 19 patients with labral lesions who were injected with hypertonic dextrose, Hauser & Orlofsky [17] suggested that this mode of management is a safer and effective procedure [17]. Although some improvements were observed, this could have been caused by the placebo effect of the injection given or the spontaneous improvement of the condition, especially with the absence of control group to assess the comparative effect of the treatment given.…”
Section: Conservative Managementmentioning
confidence: 99%